Effect of Black Carbon and Alumina Nanofluid on Thermal and Dynamic Efficiency in Upward Spraying Cooling Tower - Salman, Ekhlas A.; Makki, Hasan F.; Sharif, Adel (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
In cooling water systems, cooling towers play a critical role in removing heat from the water. Cooling water systems are commonly used in industry to dispose the waste heat. An upward spray cooling water systems was especially designed and investigated in this work. The effect of two nanofluids (Al2O3/ water, black carbon /water) on velocity and temperature distributions along reverse spray cooling tower at various concentrations (0.02, 0.08, 0.1, 0.15, and 0.2 wt.%) were investigated, beside the effect of the inlet water temperature (35 ,40, and 45 ͦ C) and water to air flow ratio (L/G) of 0.5, 0.75, and 1. The best thermal performance was found when the working solution contained 0.1 wt.% for each of Al2O3 and black carbon nanoparticles, with a maximum drop in temperature drops (i, e. range) of (16 ͦ C) and (20 ͦ C), respectively. The temperature of the tower’s outlet water was decreased as the inlet working fluid increased, and the thermal efficiency declined with the increasing of the L/G by about 5%. However, the drop in the outlet temperature caused by the nanofluid is more than that of pure water at every point by about 6 ͦ C.